The Use of Gerund and Infinitive in Students’ Recount Text : (Survey at School of Foreign Language in Bekasi) - Rizky Frihatmawati; Wawan Setiawan (Jurnal Bahasa Asing, 2022)
The aim of this research is to find and analyze the use of gerund and infinitive in students‟ recount text. This research used a qualitative approach and the method was descriptive analysis. The research population was the students of school of foreign languages and 60 samples were taken randomly from third to fifth semester. The research design used content analysis because this research employed recount texts as the source of data. It was found that the errors of using gerund for “misformation” was 68.96%, “addition” was 20.68%, “omission” was 10.34% and “misordering” was 3.44%. While, for the infinitives, there were 60% of “misinformation”, 22.22% of “addition”, 11.11% of “misordering”, and 6.66% of “omission”.